2023
DOI: 10.1021/acsanm.2c05351
|View full text |Cite
|
Sign up to set email alerts
|

Au–Ag Nanoparticles with Controllable Morphologies for the Surface-Enhanced Raman Scattering Detection of Trace Thiram

Abstract: Surface-enhanced Raman scattering (SERS) technique has been limitedly applied to the detection of trace thiram due to the weak activity of employed substrates. In this work, Au–Ag nanoparticles (NPs) with controllable morphologies are synthesized and used as SERS-active substrates for the detection of trace thiram. Porous–spiny Au–Ag NPs are synthesized with spherical Ag NPs as intermediates through in situ redox. Annular Au–Ag NPs can be further obtained by heating porous–spiny Au–Ag NPs. Here, the morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…It can be observed that distinct Raman peaks are present at 938, 1143, 1378, and 1503 cm –1 . By comparison, these peaks closely match the characteristic peaks of thiram mentioned in the literature (peak assignments are detailed in Table S1). The detection of up to 10 –8 M concentrations of thiram, the relationship between the Raman intensity at 1378 cm –1 of thiram, and the logarithm of its concentration are fitted, as shown in Figure d, revealing a good linear correlation.…”
Section: Resultssupporting
confidence: 79%
“…It can be observed that distinct Raman peaks are present at 938, 1143, 1378, and 1503 cm –1 . By comparison, these peaks closely match the characteristic peaks of thiram mentioned in the literature (peak assignments are detailed in Table S1). The detection of up to 10 –8 M concentrations of thiram, the relationship between the Raman intensity at 1378 cm –1 of thiram, and the logarithm of its concentration are fitted, as shown in Figure d, revealing a good linear correlation.…”
Section: Resultssupporting
confidence: 79%
“…The surface-enhanced Raman substrate is a prime example in the field of functional materials fabrication. Surface-enhanced Raman spectroscopy (SERS) is a technique that enhances the Raman scattering signals of target molecules on specially prepared noble metal substrates, mainly Au and Ag. The surface enhancement effect, high sensitivity, real-time performance, and nondestructive nature of SERS technology make it an effective TNT detection method. , Nowadays, various methods utilizing SERS technology have been developed for TNT detection. Researchers have created SERS substrates using 2D materials and precious metal particle composites by the in situ growth of Au nanoclusters on MG fibers .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the design of metal nanocrystals capable of generating intense EM fields is of paramount importance. The plasmon-induced EM enhancement of these metal nanocrystals is significantly influenced by their shape, size, and morphology. Many types of metal structures have been synthesized to facilitate efficient SERS detection, encompassing nanosphere, nanorods, nanotriangles, nanowire, and so on. However, the high EM field intensity of these metal nanocrystals is predominantly located at the high-curvature surface due to the lightning rod effect; many flat surfaces on this structure have limited EM enhancement under light excitation, thereby leading to low SERS efficiency. Many efficient means have been proposed to optimize the EM enhancement of metal structures, including the growth of metal nanoparticles with rough surface, the fabrication of branched gold nanostars, and the construction of multilayered and hollow structures. , These approaches offer valuable insights for the design of metal nanocrystals with substantial EM enhancement and enhanced SERS sensitivity.…”
Section: Introductionmentioning
confidence: 99%